Analisis Customer Based Brand Equity Terhadap Loyalitas Konsumen Pada Richesee Factory - Uktafiya Nurhayati; Nurholisah; Syamsul Hidayat (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
This research aims to examine the influence of customer based brand equity on consumer loyalty with the research object being the Fast Food Resto Rhiceese Factory in Serang City. The results of this research include Based Brand Equity on consumer loyalty at the Rhiceese Factory fast food restaurant in Serang City. The case study at Richesee Factory Indonesia, this research uses quantitative methods and is then analyzed using validation and reliability tests, multiple regression analysis, hypothetical tests using SPPS. In this variable test table, the results of data management based on the data table show that all statement items in the Brand Equity questionnaire are declared valid, while in this variable test table, the results of data management based on the data table show that all statement items in the Loyalty questionnaire are declared valid. The reliability statistics table shows the results of the analysis from the reliability test with Cronbach's Alpha = 0.878 out of 9. The number of items is a moderate value so that this questionnaire is said to be consistent (reable). The influence of customer based brand equity X1 in influencing each additional variable Y, consumer loyalty is influenced by other factors.